Efficacy of zero-valent copper (Cu-0) nanoparticles and reducing agents for dechlorination of mono chloroaromatics - Raut, Sandesh S.; Kamble, Sanjay P.; Kulkarni, Prashant S. (Chemosphere, 2016)
The zero-valent copper (Cu-0) nanoparticles were prepared by chemical reduction method. The morphology of nanoparticles was investigated by using X ray diffraction, scanning electron microscopy-energy dispersive X ray, UV-visible spectrophotometer and Brunauer-Emmett-Teller surface area analyser. The Cu-0 nanoparticles along with reducing agents, NaBH4/5% acidified alcohol were used for the dechlorination of chloroaromatics at room temperature. Chlorobenzene (Cl-B), chlorotoluene (Cl-T), chloropyridine (Cl-Py) and chlorobiphenyl (Cl-BPh) were selected as the contaminants. The effect of various operating parameters such as pH, concentration of the catalyst and reducing agent (NaBH4), and recycling of the catalyst on dechlorination were studied. Nearly complete dechlorination of all the chloroaromatics were achieved in the presence of Cu-0 nanoparticles (2.5 g L-1) and NaBH4 (1.0 g L-1.) within 12 h. On the contrary, approximately 70% of dechlorination was observed in the presence of 5% acidified alcohol at similar experimental conditions. The dechlorination mechanism highlighted the importance of Cu-0 nanoparticles as a surface mediator. The kinetics of the dechlorination of chloroaromatics was investigated and compared with chloroaliphatics. The dechlorination rate differed from 0.23 h(-1) (Cl-B) to 0.15 h(-1) (Cl-BPh) in the presence of Cu-0 nanoparticles and NaBH4. The effectiveness of Cu nanoparticles with NaBH4 (1 g L-1) and 5% acidified alcohol as electron donors were studied by oxidation-reduction potential and observed to be -1016 mV and -670 mV, respectively. Final products of the dechlorination were benzene, toluene, pyridine and biphenyl, as identified by gas chromatograph mass spectrometer and nuclear magnetic resonance spectroscopy. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Acidified alcohol; ChloroAromatics; Hydrodechlorination; NaBH4; Wastewater treatment; Zero-valent copper (Cu-0) nanoparticles

Screening of zero valent mono/bimetallic catalysts and recommendation of Raney Ni (without reducing agent) for dechlorination of 4-chlorophenol - Raut, Sandesh S.; Shetty, Rohit; Raju, Nikhi Maria; Kamble, Sanjay P.; Kulkarni, Prashant S. (Chemosphere, 2020)
Chlorophenol (CP) is considered as environmentally hazardous material due to its acute toxicity, persistent nature and strong bioaccumulation. The dechlorination of 4-CP was investigated by using various catalysts such as bimetallic (Fe-0/Cu-0, Al-0/Fe-0), Pd/C, Raney Ni and Fe-0 at room temperature. Among the catalysts studied, Raney Ni proved to be very economical and efficient catalyst that worked without the use of an external reducing agent. The dechlorination of 4-CP by Raney Ni was therefore further explored. Complete dechlorination of 4-CP (30 mg L-1) was achieved in 6 hat an optimum Raney Ni catalyst loading of 3 g L-1. The effect of triethylamine (TEA) and tripropylamine (TPA) was also investigated and it was observed that 100% dechlorination is possible in presence of 45 mg L-1 of TEA. The kinetics of dechlorination of 4-CP was investigated and found to be first order with a rate constant of 0.017 min(-1) at 50 degrees C, and it enhances to 0.109 min(-1) with addition of TEA. In the absence of a reducing agent, acidic to neutral pH favors dechlorination of 4-CP. The final product of dechlorination was estimated to be phenol by performing HPLC, LCMS and NMR analysis. Based on the results, a probable dechlorination mechanism of 4-CP is also proposed. It can be concluded that the catalytic hydrodechlorination is an effective and economical technique for dechlorination of 4-CP and it has a potential for the dechlorination of other toxic derivatives of chlorinated aromatics. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: 4-Chlorophenol; Cl- scavenger; Hydrodechlorination; Raney Ni; Recycling of catalyst; Without reducing agent

Improved photocatalytic efficiency of TiO2 by doping with tungsten and synthesizing in ionic liquid: precise kinetics-mechanism and effect of oxidizing agents - Raut, Sandesh S.; Kamble, Sanjay P.; Kulkarni, Prashant S. (Environmental Science and Pollution Research, 2021)
The degradation of nitroaromatics/toxic energetic compounds contaminated water is a major cause of concern. W-doped TiO2 nanoparticles (NPs) were synthesized in ionic liquid, ethyl methyl imidazolium dicyanamide (EMIM-DCA) by a solvothermal method. The developed NPs were sintered at 500 degrees C and characterized by UV-Vis-DRS, FT-IR, FE-SEM, XRD, XPS, and BET techniques. The 30-40-nm-sized NPs were subjected to photocatalytic degradation of the toxic energetic compound, tetryl (2,4,6-trinitrophenylmethylnitramine) under UV-Vis light. Various operating parameters such as the effect of concentration of catalyst, pH of feed phase, oxidizing agents, and recycling of catalyst were studied in detail. For the first time, the degradation-mechanism pathway and kinetics of tetryl were evaluated. The degradation products were precisely analyzed by using HPLC, GC-MS, and TOC techniques. The USEPA has prescribed a drinking water limit of 0.02 mg L-1, and it was found that 0.5 g of 4% W-TiO2 could totally degrade tetryl (50 mg L-1) within 8 h. The kinetic rate constant of 4% W-TiO2 was 0.356 h(-1), whereas pure TiO2 showed 0.207 h(-1).
Keywords: Ionic liquid; Nitroaromatics; Photocatalysis; Recycling of catalyst; W-doped TiO2; wastewater

Hydrodechlorination of 4-chloro-2-aminophenol into a recyclable product using Ni- and Cu-based catalysts - Shetty, Rohit R.; Raut, Sandesh S.; Kulkarni, Prashant S.; Kamble, Sanjay P. (Industrial & Engineering Chemistry Research, 2022)
The 4-chloro-2-amino phenol (4C2AP) bearing wastewater is produced while manufacturing dyes and pharma-ceutical ingredients. Ni-and Cu-based cost-effective catalysts were developed, typically characterized, and subjected to hydrodechlori-nation (HDC) of 4C2AP. The role of reducing agents, concentration, pH of wastewater, presence of salt, reaction temperature, catalyst reuse, and the kinetics was investigated. A selective makeover of 2-amino phenol (2AP) was analyzed by HPLC, LCMS, and NMR. A complete HDC of 4C2AP with remarkable selectivity (98%) toward 2AP was achieved using a Ni0 catalyst and NaBH4 at room temperature. It is observed that the alkaline condition, the presence of salt, and a high reaction temperature favor the HDC process. A maximum of 1 g L-1 of the Ni0 loading is found to be sufficient to dechlorinate the pollutant. It can be concluded that the catalytic HDC is a technically viable and inexpensive process for the conversion of 4C2AP into a valuable product, 2AP.